Răspuns :
f:R-->R
f(x)=ax+b
A(4;0) apartine Gf daca f(4)=0 , f(4) = 4a+b = 0
B(0;3) apartine Gf daca f(0)=3 , f(0) = b = 3
4a+b=0
b=3
4a+3=0
4a=-3
a= -3 / 4
f(x) = (-3/4)x + 3
f(x)=ax+b
A(4;0) apartine Gf daca f(4)=0 , f(4) = 4a+b = 0
B(0;3) apartine Gf daca f(0)=3 , f(0) = b = 3
4a+b=0
b=3
4a+3=0
4a=-3
a= -3 / 4
f(x) = (-3/4)x + 3
f(x)=ax+b
B∈Grafic⇒f(0)=3
A∈Grafic⇒f(4)=0
a*0+b=3⇒b=3
a*4+3=0
4a=-3
a=-3/4
f(x) =-3x/4+3
B∈Grafic⇒f(0)=3
A∈Grafic⇒f(4)=0
a*0+b=3⇒b=3
a*4+3=0
4a=-3
a=-3/4
f(x) =-3x/4+3